Umma Pande sebagai Ruang Edukasi dalam Membangun SDM di Pulau Sumba - Yohanes Umbu Lede (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
Human development as a whole is the basis in the educational process and is the responsibility of the government, in reality there are still school-age children who do not receive attention. This study aims to determine the role of Umma Pande as an educational space in building human resources on Sumba Island. The method used is a qualitative research method. The results showed that: theeducation carried out by Umma Pande was directed at building independence and responsibility., Thereare various kinds of limitations of school-age children, children of migrant workers and society as a whole, including: infrastructure, learning facilities, access to educational institutions, social, economic and cultural problems., Assistance is carried out to improve children s literacy and numeracy skills., A culture-based approach and local wisdom is the key to success in providing assistance and other activities in Umma Pande such as advocacy, health services and social services. Building community independence is a great hope for the presence of Umma Pande.